2013
DOI: 10.1002/pen.23737
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and numerical studies on bubble dynamics in nonpressurized foaming systems

Abstract: This work explores the influence of rheological properties on polymer foam development in nonpressurized systems. To understand the complex contributions of rheology on the mechanism of bubble growth during different stages of foam processing, visualization studies were conducted by using a polymer-foaming microscopy setup. The evolving cellular structure during foaming was analyzed for its bubble surface density, bubble size, total bubble projected area, and bubble size distribution. Morphological analysis wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 29 publications
2
16
0
Order By: Relevance
“…One of the main objectives in the production of the polymeric foams is to increase the cell density or decrease the average cell size. For this purpose, some techniques such as rapid pressure drop, 1115 high sorption pressure at low temperature, 16 selecting of high melt strength polymeric matrix, 17 polymer blending, 1820 and incorporation of nucleating agents are used. 2126 Furthermore, among nucleating agents, the nanoparticles are of more interest since they have high specific surface area and can create more heterogeneous nucleation sites into polymer matrix.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the main objectives in the production of the polymeric foams is to increase the cell density or decrease the average cell size. For this purpose, some techniques such as rapid pressure drop, 1115 high sorption pressure at low temperature, 16 selecting of high melt strength polymeric matrix, 17 polymer blending, 1820 and incorporation of nucleating agents are used. 2126 Furthermore, among nucleating agents, the nanoparticles are of more interest since they have high specific surface area and can create more heterogeneous nucleation sites into polymer matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Emami et al. 17 investigated the effect of rheological properties of polymer matrix on the foaming dynamics of polyethylene (PE) with chemical blowing agent as well. Their results showed that with increasing PE melt strength, the nucleation rate reduced while the bubbles coalescence was decreased as well.…”
Section: Introductionmentioning
confidence: 99%
“…Some comparative studies have been conducted on the bubble growth model results experimental observation in thermoplastics. [ 29–33 ] The effect of temperature, viscosity, and other materials function on the bubble growth in thermoplastics foaming process was simulated by other researchers. [ 34–37 ]…”
Section: Introductionmentioning
confidence: 99%
“…Rapid pressure drop method is mostly used to study the foaming process, 11 14 but some researchers such Iliev et al 15 and Emami et al 16 used temperature increasing method at nonpressurized conditions to examine the foaming dynamics. Generally, the rapid pressure drop method has been used more than temperature increasing method to study the foaming dynamics.…”
Section: Introductionmentioning
confidence: 99%